Desain Pengontrolan Objek 3D Interaktif Berbasis Natural User Interface Dengan Microsoft Kinect - Murhadi Murhadi (Universitas Muhammadiyah Purworejo, 2018)
Subjects of Fundamentals of Engine, has been described using a real model of a stand engine. This method is difficult because the teachers have to carry the stand engine to the classroom. To solve this problem, teacher present learning materials using sketches, images and 3D graphics of engine models. It is difficult for teachers to control the learning material to explain certain parts and this method is ineffective and inefficient for teaching process. In this paper, the pro-posed solution to control 3D engine models with hand gestures by Kinect. Therefore, it’s neces-sary to study the hand gesture that is easily operated by teacher and the usefulness of control with hand gesture. To achieve the goal of the research carried out application design, applica-tion development, internal testing and performance testing directly to the teacher as a user. Testing software that will do is the performance test and usability.To rotate the 3D engine model can be done by locking the object first by moving the right hand to the top of the right shoulder as far as 30 cm. To rotate the object to the right, the right hand to the right side of head, to turn to the left, the left hand to the left side of head, to rolling upwards, left hand on the left shoulder and to rolling downwards, the left hand to the bottom of left shoulder as far as 30 cm. To zoom in the object, right hand to the front of the right shoulder, to zoom out, the left hand to the front of left shoulder as far as 40 cm.